Impact of ISO 9000 certification in academic libraries in Malaysia : Empirical study - Taib, Che Azlan; Ahmad, Hartini; Osman, Nor Hasni (2010)
The study investigates the impact of ISO 9000:2001 certification toward employees satisfaction, the results derived from the selected academic libraries in Malaysia.. The study used the Academic Library Employee Satisfaction Questionnaire (ALESQ) to ascertain the level of library staff satisfaction of the libraries that implementing the ISO 9001into their systems. The instrument assessed seven dimensions of employee satisfaction - resources management, team building/coworkers, recognition, leadership, communication, training and job satisfaction. A total of 549 respondents were selected from 60 academic libraries, which 409 represented Public Higher Education Institute (PuHEI) and 60 represented Private Higher Education Institute (PrHEI). The study shows the overall employee satisfaction of between 5.0 and 5.4 on a 7-point scale. It showed a statistically significance difference in employees satisfaction score for 10 categories of academic library (resource management, staff recognition and job satisfaction – were statistically difference). There is a significant difference between males and females in the employees satisfaction scores.